1954
DOI: 10.1037/h0059895
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of flying success by clinical analysis of test protocols.

Abstract: "In the present study there is little doubt that the clinical assessments of beginning aviation cadets have no relationship to a criterion of adjustment in the basic flight-training program. The objective findings can hardly be ignored, and it is of utmost importance to consider the possible explanations of these results in order to appreciate fully their significance." Various explanations are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
1

Year Published

1955
1955
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 3 publications
0
26
0
1
Order By: Relevance
“…They found that best results came from a combined use of tests, recommendation forms checked by at least two people, separate interviews at least two and a half hours in length, a panel review, and a group discussion. Other authors (Hollander, 1954 ;Holtzman & Sells, 1954;Kelly & Fiske, 1951) have come to the same general conclusions: assessment for selection should increase in validity as additional independent assessmen t measures are used.…”
mentioning
confidence: 90%
“…They found that best results came from a combined use of tests, recommendation forms checked by at least two people, separate interviews at least two and a half hours in length, a panel review, and a group discussion. Other authors (Hollander, 1954 ;Holtzman & Sells, 1954;Kelly & Fiske, 1951) have come to the same general conclusions: assessment for selection should increase in validity as additional independent assessmen t measures are used.…”
mentioning
confidence: 90%
“…He found that the evidence pointed to a lack of observed reliability in t,he psychiatric diagnostic domain. Since Eysenck's review of this problem, there have been many additional studies inves-tigating psychiatric judgment (e.g., Cattell, 1957;Ellis & Sells, 1964;Holtzman & Sells, 1954;Mehlman, 1952;Schmidt & Fonda, 1956;Wallinga, 1956), but in general they have not provided evidence contrary to that of Eysenck.…”
Section: Discussionmentioning
confidence: 99%
“…Retzlaff and M. Gibertini questioned and explored the notion that a unitary personality exists among pilots through several studies of military and civilian pilots over the last thirty years (e.g., Ashman & Telfer, 1983;Fleischman, Ambler, Peterson, & Lane, 1966;Holtzman & Sells, 1954;Sells, 1956).…”
mentioning
confidence: 98%
“…The first asks whether there exists an optimal or specific pilot personality structure which has identifiable developmental roots and clear adaptive advantage for both military life and the specific demands of flying (e.g., Fine & Hartman, 1968;Fulkerson, Freud, & Raynor, 1958). The second asks whether specific personality traits can predict which pilots will succeed on various flying-and combat-related criteria (e.g., Buckey & Ridley, 1972;Fleischman et al, 1966;Holtzman & Sells, 1954;Sells, 1956). As for the second question, there is reason beyond the "right stuff' folklore to expect that successful military pilots may be distinguishable on the basis of personality.…”
mentioning
confidence: 99%
See 1 more Smart Citation